Competing in the age of digital convergence - Yoffie, David B. (Harvard Business School Press, 1997)
"The essays in this important collection examine the consequences of digital convergence on the participating companies and industries, their internal capabilities, the products and services they produce, and the way they compete. In the process, the authors reveal that the key to success for companies in this new environment will not be to engineer big technological breakthroughs or to execute grand acquisitions. Instead, the winners will be those companies that develop innovative products and services by creatively combining existing technologies with new managerial approaches."--BOOK JACKET. "Timely essays place the computer industry in historical perspective; address prospects for industry convergence; identify economic, legal, and managerial obstacles to convergence; and examine the managerial challenges facing companies in rapidly changing hardware and software environments, particularly around issues of product and process development and interfirm alliances."--Book jacket.